Subtracted from for example, 5 diminished by 4 equals 1.
1 (1x1x1 or 1x1)
8x8=64(1x1)7x7=49(2x2)6x6=36(3x3)5x5=25(4x4)4x4=16(5x5)3x3=9 (6x6)2x2=4 (7x7)1x1=1 (8x8)64+49+36+25+16+9+4+1=204Total=204
This has already been answered:The Answer is 3,263,422n*(n+1) = x (where n equals the previous x)1*(1+1) = 2 2*(2+1) = 66*(6+1) = 4242*(42+1) = 18061806*(1806 +1) = 3263442Each term is being squared then added plus the original amount.So the second term will be equal to the first term squared, then add the first term.In an equation (n^2) + n , where n is the previous term.So the next term is 3,263,442
1x1=1 because if there is 0x1 it will be 0 because that why 1x1=1
0 and 1. 1x1 = 1. The answer is itself!
1x1 + 1x1 + 1x1 + 1x1 + 1x1 = 5
Yes because basically you're multiply 1 one time so the answer is 1.
tanga ka pam
1x1=1 So 1+70=71 71 is the answer
if its 1x1 its 1. If its 99x1 its 99. so whatever number x one equals that number
1x1=1 because there are 1 1s